1999
DOI: 10.1103/physrevb.59.4215
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature heat-capacity studies ofR2Ni3Si5

Abstract: We report here our low temperature (2Ϫ30 K) heat capacity, C p measurements of R 2 Ni 3 Si 5 (R ϭPr, Nd, Sm, Gd-Ho). Large peaks in heat capacity data at magnetic transition temperatures (T N ) confirm the bulk nature of magnetic order in these compounds. In Nd 2 Ni 3 Si 5 , Gd 2 Ni 3 Si 5 , and Dy 2 Ni 3 Si 5 , magnetization studies indicated only one magnetic transition, whereas, heat-capacity data show two transitions. T N of the heavier rare-earth member, Tb 2 Ni 3 Si 5 , showing significant deviation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, magnetoresistance anomalies in Gd-alloys have been studied in detail and documented well. [34][35][36][37][38][39] It is interesting to note that the temperature dependence of electrical resistivity of Gd-alloys like GdCu 2 Si 2 and GdNi 2 Si 2 resemble that of Gd 3 Ir 4 Sn 13 . 34 The MR is observed to be positive for GdCu 2 Si 2 above the Néel temperature.…”
Section: Discussionmentioning
confidence: 99%
“…However, magnetoresistance anomalies in Gd-alloys have been studied in detail and documented well. [34][35][36][37][38][39] It is interesting to note that the temperature dependence of electrical resistivity of Gd-alloys like GdCu 2 Si 2 and GdNi 2 Si 2 resemble that of Gd 3 Ir 4 Sn 13 . 34 The MR is observed to be positive for GdCu 2 Si 2 above the Néel temperature.…”
Section: Discussionmentioning
confidence: 99%
“…La3Ni4Si4 [6,7]. It is interesting that most of the R2Ni3Si5-family members exhibit antiferromagnetic phase transitions at temperatures TN ≤ 30 K and the magnetic moments, originating only from the rare-earth atoms because the nickel atoms remain non-magnetically ordered (NMO) [8][9][10][11][12][13][14]. In antiferromagnetically ordered (Pr;Dy;Ho)2Ni3Si5 systems, an existence of also short-range ferromagnetic (FM) correlations has been postulated, based on observations of an anomalous behavior of magnetoresistivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…5. Although a hump of specific heat below T N is often observed in Gd-based compounds, 22,23 it is unusual in Ce-based compounds. Blanco et al 28 showed that C mag of an amplitude-modulated moment Gd-based system below T N shows a hump with a decrease in the peak height at T N .…”
Section: Resultsmentioning
confidence: 99%